Robust Adaptive Multiple-Input Multiple-Output Radar Array Beamforming Using Advanced Generalized Sidelobe Canceller Against Random Scenario Mismatches - Cheng-Jie Wang; Ju-Hong Lee (IEEE Access)
Nowadays, one of the core issues regarding multiple-input multiple-out (MIMO) radar is its robustness against scenario mismatches owing to its sensitivity to array scenario mismatch. This paper presents a method to enhance the performance of an advanced generalized sidelobe canceller based MIMO radar beamformer recently presented in the literature in dealing with scenario mismatches. We formulate an optimization problem of maximizing the output power gain of the beamformer for effectively finding the optimal estimate of the desired signal’s direction angle. An efficient iterative algorithm is proposed based on a well-known early late gate synchronization to solve the optimization problem without requiring complicated algorithmic complexity. The proposed method is not only efficient but also effective to cure the performance deterioration under random multiple scenario mismatches. The convergence and computation complexity regarding the proposed method are analyzed. Simulation results are provided for confirmation and making comparisons with the existing robust methods.